2017
DOI: 10.1097/ccm.0000000000002556
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Harm in the ICU—Building a Culture of Safety and Engaging Patients and Families

Abstract: Efforts to establish a culture of safety and meaningfully engage patients and families should form the foundation for all safety interventions in the ICU. This review describes an approach that integrates components of several proven quality improvement methodologies to enhance safety culture in the ICU and highlights opportunities to include patients and families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
0
14
0
2
Order By: Relevance
“…These traits can lead to situations in which patient safety is a rare subject of communication between patients and professionals in everyday clinical practice (Martin, Navne, & Lipzak, ). For this reason, nurse leaders have a critical role in developing the structure for supporting PP in PS (Fisher, Jones, & Verran, ; Jangland et al, ; Thornton et al, ). If patient safety issues are not customarily addressed in the wards, patients are unsure of their roles and expected actions (Ocloo & Matthews, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These traits can lead to situations in which patient safety is a rare subject of communication between patients and professionals in everyday clinical practice (Martin, Navne, & Lipzak, ). For this reason, nurse leaders have a critical role in developing the structure for supporting PP in PS (Fisher, Jones, & Verran, ; Jangland et al, ; Thornton et al, ). If patient safety issues are not customarily addressed in the wards, patients are unsure of their roles and expected actions (Ocloo & Matthews, ).…”
Section: Discussionmentioning
confidence: 99%
“…Patient participation and patients’ views on PS are important for efficient identification of effective interventions for promotion of safe care (Ringdahl, Chaboyer, Ulin, Bucknall, & Oxelmark, ). Improving safety requires an organisational culture that enables and prioritizes safety and, above all, a commitment to safety at all organisational levels from frontline workers to managers and executives (Fisher, Jones, & Verran, ; Thornton et al, ). A robust safety culture also requires active leadership.…”
Section: Introductionmentioning
confidence: 99%
“…Across medical specialties, preventable patient harm is more prevalent in the ICU [6]. ICUs are complex environments where the severity of illnesses, the high levels of stress, the variety of therapies and routes of administration make medical errors and deaths due to preventable harm more common [7]. In the Critical Care Safety Study [8], Rothschild et al found a daily rate of 0.8 adverse events and 1.5 serious errors for 10 ICU beds, with a rate for serious errors of 149.7 per 1000 patient-days.…”
Section: Epidemiology Of Adverse Eventsmentioning
confidence: 99%
“…The quality of the relationships between nurses, doctors, and other staff working in perioperative settings affects patient outcomes: good teamwork, when team members communicate efficiently and respect each other while working toward a common goal, allows the team to reduce complications and mortality [7]. Conversely, communication failures and bad relationships can lead to increased risk of error, length of stay, resource use, caregiver dissatisfaction, and turnover.…”
Section: Communication and Teamworkmentioning
confidence: 99%
“…O envolvimento do paciente tem vindo ainda a ser reconhecido como factor de redução dos custos de saúde e de maior eficiência nos cuidados, quer na fase de diagnóstico, quer no tratamento (Hibbard, Green 2013;WHO2016). Constituindo um determinante importante da relação de colaboração entre o profissional de saúde e os pacientes e/ou seus familiares, o envolvimento do paciente está ainda relacionado com maior transparência na comunicação, menor número de litígios por má prática médica (Studdert et al 2006) e diminuição de eventos adversos (Thormton et al 2017).…”
Section: Considerações Finaisunclassified